Developing a Competency Framework for Cyber Intelligence Professionals in Indonesia: An Analytical Perspective - Dwi Andriarto (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2026)
The advancement of information and communication technology has led to logical consequences in the form of increasingly complex threats to national security, thus requiring an integrated and comprehensive role of cyber intelligence in addressing these various cyber threats. The management of cyber intelligence in Indonesia is still considered suboptimal due to the lack of basic references in the form of conceptual frameworks or competencies related to cyber intelligence. The purpose of this research is to provide an understanding of the framework of cyber intelligence and to develop a competency framework for cyber intelligence professionals in Indonesia, encompassing various necessary skills and expertise. The method used in this research is qualitative, collecting data through literature studies related to the research object and subsequently analyzed using descriptive analytical techniques. The results show that there are at least two cyber intelligence frameworks that can serve as a basis for use in Indonesia, namely the SEI model from Carnegie Mellon University and the FIRST Cyber Threat Intelligence SIG model. In addition, the Indonesian government may consider five core competencies needed to enhance the capabilities of domestic cyber intelligence, namely technical competency, analytic competency, knowledge management (information) competency, contextual domain competency, and communication and organizational competency. These five competencies need to be formulated clearly and specifically, considering the dynamics of cybersecurity domestically and the international geopolitical constellation.